KECERDASAN INTERPERSONAL, RASA SYUKUR, DAN PERILAKU PROSOSIAL PADA REMAJA - Finisia Putri Melati; Effy Wardati Maryam (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Prosocial behavior is very important and must be owned by every teenager. The research objective is to determine the relationship between interpersonal intelligence, gratitude, and prosocial behavior. Where currently many teenagers have low prosocial behavior. Meanwhile, this prosocial behavior will have a positive impact on both oneself and others, especially during the adolescent phase when they begin to adapt and establish good relationships with other people or a new environment. The population of this study was high school students of school X with a total of 760 and a sample of 254 students. The technique for taking samples is purposive sampling technique. Research data collection techniques using interpersonal intelligence scale, gratitude, and prosocial behavior. To find out the relationship between interpersonal intelligence and gratitude variables with prosocial behavior variables, we used the product moment correlation statistical method with the help of SPSS 25. This study produced a significant positive relationship between interpersonal intelligence and prosocial behavior, and gratitude with prosocial behavior, namely (p) 0.000 <0.05. In this study the results of the correlation test between interpersonal intelligence and gratitude towards prosocial behavior also have a significant positive relationship. It is hoped that this research can provide information to future researchers and school agencies to improve prosocial behavior because it is important for the stage or phase of its development.